Pengembangan Media Pembelajaran Berbasis Android untuk Meningkatkan Pemahaman Matematis Siswa dalam Penerapan Model Problem Based Learning - Natasya Isabel Br. Siahaan; Tiur Malasari Siregar (Jurnal Mahasiswa Kreatif, 2024)
Based on the results of the needs analysis in the learning process, a development of learning media is needed. This research aims to create this product to be more valid, practical and effective in improving students' mathematical understanding. This research and development uses the ADDIE (Analyze, Design, Development, Implementation, and Evaluate) development model. The subjects of this research were 30 students of class X Science 1 at SMA Methodist 7 Medan. The research results show that the Android-based learning media developed has obtained a very high level of validity, with an average percentage of 90.38% according to material experts, 87.77% according to media experts, then 90.90% according to lesson plan validators and results. Validation from experts on pre-test and post-test questions showed a percentage of 92.70% and 91.67%, respectively included in the "very valid" criteria. Positive responses were also found from teachers and students during small group and large group trials, with an average score of 96% from teachers, 94.4% from small groups, and 90.2% from large groups. This shows that this media is very practical to use in the learning process. Apart from that, the results of implementing this interactive learning media also show its effectiveness with the average percentage of responses to the effectiveness of learning media by students obtained at 92.23%. The classical learning completion level reached 96.67%, and the effectiveness questionnaire obtained an average percentage of 86.67%. The increase in students' mathematical understanding can be categorized as moderate improvement. Based on this research data, it can be concluded that the Android-based learning media that we have developed has met the criteria of being valid, practical and effective in improving students' mathematical understanding.